Molecular testing to optimize therapeutic decision making in advanced colorectal cancer - Semrad, Thomas J.; Kim, Edward J. (Journal of Gastrointestinal Oncology; Vol 7, Supplement 1 (April 02, 2016): Journal of Gastrointestinal Oncology (Gastrointestinal Oncology: Current Concepts and Emerging Diagnostic and Therapeutic Strategies), 2015)
Colorectal cancer (CRC) is a leading cause of cancer death in the United States. In recent years, therapeutic advances have prolonged the survival of patients with advanced disease. Along with the addition of new treatments, an increasing body of literature explores the potential benefit of using molecular testing to define tumor, circulating, or host biomarkers of benefit to specific treatment strategies. At present, testing for specific mutations in exons 2, 3, and 4 of KRAS and NRAS has become accepted practice to select patients for treatment with epidermal growth factor receptor (EGFR)-targeted agents. Additionally, testing for the BRAF V600E mutation is used to refine decisions based on patient prognosis. The presence of the uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) *28 polymorphism is associated with toxicity from irinotecan, although it has not been universally applied. Nonetheless, molecular markers to predict response and toxicity of cytotoxic therapy are evolving. While the development of selection biomarkers for antiangiogenic treatments has not proved fruitful to date, improved development strategies and novel targeted agents are anticipated to revolutionize the approach to treatment of advanced CRC in the near future. This review summarizes currently available data to select treatment strategies in patients with advanced CRC.